Legal Pluralism Perspective in Prosecuting Perpetrators of Bribery and Gratuities Corruption Crimes: Perspektif Pluralisme Hukum dalam Penindakan Pelaku Tindak Pidana Korupsi Suap dan Gratifikasi - Ginting, Jamin; Talbot, Patrick; Darryl, Erdick (Jurnal Konstitusi, 2023)
The act of giving and receiving has been a practice since feudal times. Gifts or tributes to kings or officials, among other forms of giving, are part of traditional customs and are considered social etiquette. To address these issues, the authors analyze the theory of criminal liability, lawlessness, legal pluralism, and the legal system. This research uses a normative juridical research methodology. The findings reveal that there are no clear boundaries concerning regulations related to bribery and gratuities, specifically regarding gifts or promises in which civil servants or public officials can or cannot accept. The application of the bribery and gratuity clause was misdirected, resulting in innocent individuals being punished while the guilty were acquitted.